Amitai Etzioni papers - Etzioni, Amitai
Correspondence, administrative and subject files, research notes, project proposals, position papers, essays, and other writings, newsletters, newspaper clippings, printed material, and other papers documenting Etzioni's career as a professor of sociology at George Washington and Columbia universities, at the Center for Policy Research, and as an advisor to President Jimmy Carter. Topics include the Vietnamese conflict, student protest movement, social policy, energy, politics and government, education, family issues, capitalism, civil rights, mental health, taxation, science and technology, poverty, violence, economics, and voluntarism.
Educator and sociologist. Born 1929. Full name: Amitai Werner Etzioni.
Collection material in English, with Hebrew.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Carter, Jimmy, -- 1924-; Center for Policy Research (U.S.); Columbia University -- Faculty; George Washington University -- Faculty; Capitalism -- United States; Civil rights -- United States; Education -- United States; Energy policy -- United States; Families -- United States; Mental health -- United States; Poverty -- United States; Science -- United States; Sociology; Technology -- United States; Student movements; Taxation -- United States; Vietnam War, 1961-1975.; Violence -- United States; Voluntarism -- United States; United States -- Economic conditions; United States -- Politics and government -- 1977-1981.; United States -- Social conditions -- 1945-